Tratamiento fisioterapéutico en la amputación del miembro inferior - Jaque Jaque, Katherine Magali (2022)
ABSTRACT The present investigation was developed with the bibliographic review modality, to analyze the physiotherapeutic treatment in lower limb amputation, through scientific evidence to provide updated information on the effects and importance. Lower limb amputation has an incidence 7 to 8 times higher than upper limb amputations, with a 60% prevalence in men. Being the main causes: vascular diseases, trauma, or as the only option to remove a tumor. When individuals undergo an amputation, they experience physical and psychological changes, within which the loss of physical capacity leads them to decrease their ability to walk and in activities of daily living. Therefore, the main purpose of the physiotherapeutic process in amputees is functional recovery that achieves maximum autonomy for the patient. The compilation of the information was carried out in the following databases PubMed, Scielo, Google Scholar, ProQuest, Elsevier, and Cochrane, obtaining 68 articles of which 35 were used. After the investigation and with the respective discussion of the authors, it is concluded that the different physiotherapeutic treatments applied in lower limb amputees have proven to be beneficial and with optimal results either with short or long-term methods, likewise, the importance of elementary physiotherapeutic rehabilitation is emphasized. Key words: Physiotherapeutic treatment, lower limb amputation, transtibial, transfemoral, amputation rehabilitation. Firmado electrónicamente por: JHON JAIRO INCA Reviewed by: Lcdo. Jhon Inca Guerrero. ENGLISH PROFESSOR C.C. 0604136572